Pertanggungjawaban Pribadi Direktur PT Dalam Kepailitan PT Sri Rejeki Isman Tbk (Sritex) Ditinjau Berdasarkan UU Perseroan Terbatas - Luthfiyyah Pahlevi Ramadhani; Arief Suryono (Indonesian Publication Center, 2026)
This study aims to analyze the form of board of directors’ personal liability in the bankruptcy of PT Sritex, particularly in relation to unlawful acts on financial management negligence and harmful decision-making towards the company, such as financial statements manipulation to obtain working capital loans and the misuse of loan funds for personal interests, which resulted in corporate losses or bankruptcy based on Law Number 40 of 2007 concerning Limited Liability Companies. This research constitutes normative legal research employing a statutory approach. The legal materials used consist of primary data in the form of regulations related to Limited Liability Companies and bankruptcy, as well as secondary data derived from books, scientific journals, and other academic writings. The study is prescriptive-analytical in nature. The results indicate that the Company Law provides limited liability protection as long as directors exercise their authority in accordance with applicable regulations. However, if directors exceed their authority (ultra vires) for personal interests and causing losses, the doctrine of piercing the corporate veil may be applied to impose personal liability. Directors may be held personally liable if they are proven to have committed fault or negligence and have acted beyond their authority, failing to fulfill the principles of fiduciary duty and duty of care, resulting in company losses, creditors, or third parties. Based on the Company Law and the Indonesian Civil Code, if directors are proven to have committed unlawful acts or negligence in performing their duties, they may be subject to civil claims, and their personal assets may be seized as part of the bankruptcy estate. Civil liability may be imposed for losses arising from decisions related to working capital loans that do not comply with established procedures, including those set forth in the Articles of Association and applicable laws.